Invention of Learning Model PAKIM Based Karo Culture Nganting Manuk - Nuraini Sri Bina; Rusmini Rusmini; Yulia Fitri; Hizmi Wardani (Universitas Hamzanwadi, 2025)
Education functions in shaping the character of the nation, improving the quality of human resources, advancing science and technology, developing creativity and innovation, preserving local culture and wisdom, building careers and jobs, fostering environmental awareness and improving community welfare. Based on a survey of National Exam scores for mathematics subjects in Karo Regency, Indonesia is still in the bad category, namely an average score of 39.56 for 2019. One of the causes of this situation is the lack of applied learning models, especially culture-based learning models. Therefore, the purpose of this research is to invent a learning model based on one of the cultures in Indonesia, namely the Karo culture Nganting Manuk. The method used in this research is development research with the Plomp model. The result of this study was the discovery of a valid, practical and effective PAKIM learning model based on Karo Culture. The practical PAKIM learning model, based on the model's implementation criteria, received a “high” category. The PAKIM model met two effectiveness criteria: achieving the Minimum Competency (KKM) of 86.11% and achieving a positive student response of 96.2%. This learning model has the advantage of being able to support the educational function, namely preserving local culture and wisdom because it is integrated with Karo culture. This research has three categories of novelty, namely invention novelty, improvement novelty and refutation novelty.